A review on current status of capacity control techniques for two-phase ejectors. (November 2020) - Gullo, Paride; Kærn, Martin Ryhl; Haida, Michal; Smolka, Jacek; Elbel, Stefan
Highlights: Two-phase ejectors are expected to lead to a significantly more sustainable future. Benefits from two-phase ejectors strongly depend on their capacity control strategy. Capacity control mechanisms for two-phase ejector are comprehensively reviewed. Two-phase ejectors can be capacity controlled in large- and medium-scale units. Capacity control method for small-scale units still requires a major breakthrough. Abstract: The adoption of highly efficient vapour-compression heating, ventilation, air conditioning and refrigeration (HVAC&R) systems is compulsory to achieve a low-carbon society. Expansion work recovery using a two-phase ejector is widely recognized as one of the most promising measures to improve the energy efficiency of HVAC&R units. This holds true for all operation conditions provided that an effective capacity control technique is implemented. In this work a thorough critical review on the current status of the presently available capacity control strategies for two-phase ejectors was carried out. In addition, their pros and cons as well as the comparison of their performance were reported. It was concluded that two-phase ejectors can be properly capacity controlled in large- and medium-scale vapour-compression units. However, a suitable capacity control mechanism for small-scale vapour-compression solutions still requires a major breakthrough and is being intensively discussed among experts in the field.